Multi-Domain Touchscreen-Based Cognitive Assessment of C57BL/6J Female Mice Shows Whole-Body Exposure to 56Fe Particle Space Radiation in Maturity Improves Discrimination Learning Yet Impairs Stimulus-Response Rule-Based Habit Learning - Soler, Ivan; Yun, Sanghee; Reynolds, Ryan P.; Whoolery, Cody W.; Tran, Fionya H.; Kumar, Priya L.; Rong, Yuying; DeSalle, Matthew J.; Gibson, Adam D.; Stowe, Ann M.; Kiffer, Frederico C.; Eisch, Amelia J. (Frontiers in Behavioral Neuroscience, 2021)
Astronauts during interplanetary missions will be exposed to galactic cosmic radiation, including charged particles like 56Fe. Most preclinical studies with mature, “astronaut-aged” rodents suggest space radiation diminishes performance in classical hippocampal- and prefrontal cortex-dependent tasks. However, a rodent cognitive touchscreen battery unexpectedly revealed 56Fe radiation improves the performance of C57BL/6J male mice in a hippocampal-dependent task (discrimination learning) without changing performance in a striatal-dependent task (rule-based learning). As there are conflicting results on whether the female rodent brain is preferentially injured by or resistant to charged particle exposure, and as the proportion of female vs. male astronauts is increasing, further study on how charged particles influence the touchscreen cognitive performance of female mice is warranted. We hypothesized that, similar to mature male mice, mature female C57BL/6J mice exposed to fractionated whole-body 56Fe irradiation (3 x 6.7cGy 56Fe over 5 days, 600MeV/n) would improve performance vs. Sham conditions in touchscreen tasks relevant to hippocampal and prefrontal cortical function (e.g. location discrimination reversal [LDR] and extinction, respectively). In LDR, 56Fe female mice more accurately discriminated two discrete conditioned stimuli relative to Sham mice, suggesting improved hippocampal function. However, 56Fe and Sham female mice acquired a new simple stimulus-response behavior and extinguished this acquired behavior at similar rates, suggesting similar prefrontal cortical function. Based on prior work on multiple memory systems, we next tested whether improved hippocampal-dependent function (discrimination learning) came at the expense of striatal rule-based learning (visuomotor conditional learning). Interestingly, 56Fe female mice took more days to reach criteria in this striatal-dependent rule-based test relative to Sham mice. Together, our data support the idea of competition between memory systems, as a 56Fe-induced decrease in striatal-based learning is associated with enhanced hippocampal-based learning. These data emphasize the power of using a touchscreen-based battery to advance our understanding of the effects of space radiation on mission-critical cognitive function in females, and underscore the importance of preclinical space radiation risk studies measuring multiple cognitive processes, thereby preventing NASA’s risk assessments from being based on a single cognitive domain.